2006
DOI: 10.1243/09544054jem647
|View full text |Cite
|
Sign up to set email alerts
|

Operation sequencing optimization using a particle swarm optimization approach

Abstract: Operation sequencing is one of the crucial tasks in process planning. However, it is an intractable process to identify an optimized operation sequence with minimal machining cost in a vast search space constrained by manufacturing conditions. In this paper, the complicated operation sequencing process has been modelled as a combinatorial optimization problem, and a modern evolutionary algorithm, i.e. the particle swarm optimization (PSO) algorithm, has been employed and modified to solve it effectively. Initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 19 publications
0
60
0
1
Order By: Relevance
“…The fourth part is presented by Guo et al [26] to test the computational efficiency of PSO and comparison experiments of PSO with GA and SA are also conducted. This part consists of 11 features and 14 operations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fourth part is presented by Guo et al [26] to test the computational efficiency of PSO and comparison experiments of PSO with GA and SA are also conducted. This part consists of 11 features and 14 operations.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, many metaheuristic algorithms have been applied to process planning problem due to their superiority in solving combinatorial optimization problems. These algorithms can be categorized as genetic algorithm (GA) [13][14][15][16][17][18][19][20][21], simulated annealing (SA) [22,2,23], tabu search (TS) [24,25], particle swarm optimization (PSO) [26] and ant colony optimization (ACO) [10].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Advance it was examined by Krishna and Rao [12] utilizing Ant colony algorithm (ACA) and found that the computational time has significantly decreased. Guo et al [13] connected particle swarm optimization (PSO) for task sequencing issue, and inferred that there is as yet potential for assist change in calculation efficiency and optimality if presenting new administrators and qualities of different calculations. Besides, Salehi et al [15] again applied a genetic algorithm to create the ideal grouping of assembling tasks in fundamental and point by point planning.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, process planning in products disassembly has also been considered. Other typical research regarding process planning can be found in [6,7].…”
Section: Introductionmentioning
confidence: 99%